THE INFLUENCE OF INCOME, UNEMPLOYMENT, EDUCATION AND DEMOCRACY ON HAPPINESS IN INDONESIA - Elita Safitria; Nairobi; Arivina Ratih Yulihar Taher (ZILLZELL MEDIA PRIMA, 2025)
This study aims to find out the extent to which economic, social and political factors affect the level of happiness of people in Indonesia. In this study, economic factors are represented by GDP and unemployment rates, social factors are represented by average school age and political factors are represented by democracy levels. Using panel data from 34 provinces in 2014, 2017, and 2021, using a Fixed Effect Model (FEM) approach. The results of the analysis showed that the variables of GDP and unemployment rate had a significant negative relationship with the happiness index. On the other hand, the average length of school shows a negative positive impact. Meanwhile, the level of democracy does not show a statistically significant influence. This model has an R-squared value of 0.740 which indicates that almost 74% of the variation in the happiness index can be explained by the variables in the model. These findings emphasize the importance of inclusive economic growth, reducing the unemployment rate, and equitable access to education in an effort to improve the subjective welfare of people in Indonesia.